2023
DOI: 10.1007/s00018-022-04666-8
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic radiation exposure causes multifaceted neurocognitive impairments

Abstract: Technological advancements have facilitated the implementation of realistic, terrestrial-based complex 33-beam galactic cosmic radiation simulations (GCR Sim) to now probe central nervous system functionality. This work expands considerably on prior, simplified GCR simulations, yielding new insights into responses of male and female mice exposed to 40–50 cGy acute or chronic radiations relevant to deep space travel. Results of the object in updated location task suggested that exposure to acute or chronic GCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
(93 reference statements)
2
18
0
Order By: Relevance
“…Also, the lack of effect on object recognition memory in our current work is striking given that the most commonly reported behavioral deficit after whole-body charged-particle radiation is seen in novel object recognition (NOR) assessments (Cacao and Cucinotta 2019). However, prior work with female mice also shows intact NOR 3.5 mon after chronic (50cGy) or acute (40 cGy) 33-GCR; notably, male mice in that study had disrupted NOR (Alaghband et al 2023). Thus, future work should test if 33-GCR-induced deficits in NOR are indeed sex-specific.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Also, the lack of effect on object recognition memory in our current work is striking given that the most commonly reported behavioral deficit after whole-body charged-particle radiation is seen in novel object recognition (NOR) assessments (Cacao and Cucinotta 2019). However, prior work with female mice also shows intact NOR 3.5 mon after chronic (50cGy) or acute (40 cGy) 33-GCR; notably, male mice in that study had disrupted NOR (Alaghband et al 2023). Thus, future work should test if 33-GCR-induced deficits in NOR are indeed sex-specific.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, we conclude that this dose (∼75cGy total in 1 day) of whole-body 33-GCR does not influence behavioral pattern separation assessed via LDR, at least at this time examined post-IRR. In contrast, other work shows that female C57BL/6J mice that received either acute or repeated exposure to 33-GCR (∼50 cGy total over 24 days) had worse behavioral pattern separation relative to control female mice, as assessed in the OUL (object in updated location) test (Alaghband et al . 2023); the authors state such changes did not “manifest” in the male mice.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Animal models, subjected to charged particles ranging from protons to the heavier ionized nuclei typically found in the galactic-cosmic ray (GCR) spectrum, have revealed that such exposures lead to neurocognitive complications involving a range of associated pathologies ( 3 ). Importantly, space relevant doses ≤50 cGy of nearly any individual or combination of ions have now been found to elicit persistent neuroinflammation, degradation of mature neurons throughout the brain, and impairments in learning and memory along with a host of mood disorders ( 4 , 5 ). Even more concerning for space agencies is that most of these cosmic radiation-induced disruptions in the central nervous system (CNS) functionality do not appear to resolve with time ( 1 ), even over the course of one year following exposure ( 2 , 6 ).…”
Section: Introductionmentioning
confidence: 99%